2011
DOI: 10.1038/leu.2011.140
|View full text |Cite
|
Sign up to set email alerts
|

TAL1/SCL is downregulated upon histone deacetylase inhibition in T-cell acute lymphoblastic leukemia cells

Abstract: The transcription factor T-cell acute lymphocytic leukemia (TAL)-1 is a major T-cell oncogene associated with poor prognosis in T-cell acute lymphoblastic leukemia (T-ALL). TAL1 binds histone deacetylase 1 and incubation with histone deacetylase inhibitors (HDACis) promotes apoptosis of leukemia cells obtained from TAL1 transgenic mice. Here, we show for the first time that TAL1 protein expression is strikingly downregulated upon histone deacetylase inhibition in T-ALL cells. This is due to decreased TAL1 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…23,47,48 In contrast, the survival of late erythroid cells 20 and of monocytes 39 does not depend on SCL function, indicating that SCL may have different functions in progenitors and mature cells. We have previously shown that Kit is a target of transcription activation by SCL.…”
Section: Scl and Cell Survivalmentioning
confidence: 99%
“…23,47,48 In contrast, the survival of late erythroid cells 20 and of monocytes 39 does not depend on SCL function, indicating that SCL may have different functions in progenitors and mature cells. We have previously shown that Kit is a target of transcription activation by SCL.…”
Section: Scl and Cell Survivalmentioning
confidence: 99%
“…TAL1 expression is shut down upon T-cell lineage commitment21 and its aberrant expression in committed T-cell precursors is associated with leukemogenesis, with TAL1 overexpression occurring in more than 60% of T-ALL patients222324. Although a considerable number of TAL1 downstream target genes have been identified to date1223252627282930313233343536 validation and characterization of their functional involvement in TAL1-mediated leukemogenesis remain fragmentary.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Survival rates at 5 years for children and adolescents with T-ALL are 70-75%, whereas for adults the rates are 35-40%. 6,7 Therefore, there is a need for novel and less toxic treatment strategies targeting aberrantly activated signaling pathways that increase proliferation, survival and drug resistance of T-ALL cells.…”
Section: Introductionmentioning
confidence: 99%